(untitled) (Proceedings of the International Conference on Public Health, 2021)
This study was conducted to determine the nutritional status of primary school children with the mid-day meal program. A cross-sectional study was conducted in 05 primary schools with the mid-day meal program of Sundarganj Upazila of Gaibandha district from January 01 to December 31, 2017. A total of 357 primary school children of class IV and class V were selected using a systematic sampling technique. A semi-structured questionnaire was used to collect data from the school children of mid-day meal program schools. The anthropometric measurements such as weight, height and MUAC were measured for each child individually. Then weight and height were used to calculate the Z score to interpret nutritional status. The mean age of children was 10.83±1.03 years. The mean weight and mean height of children were 32.40±7.21 kg and 141.22±8.52 cm respectively, and the mean MUAC was 19.65±2.31 cm. It was revealed that 91.3% of children were normal by Height for Age (HAZ) and 89.1% were normal by Weight for Age (WAZ), and the remaining children were stunted and underweight respectively. 78.8% of children used anthelminthic drugs regularly and among them, 74.3% were normal in Weight for Age Z score. Socioeconomic status, dietary habit, physical activity and anthelminthic use by the child were found to be determinants of their nutritional status.